Effect of abrasive tools on surface finishing when grinding mild steel - Abd Faiz, Muhammad (2010)
The main purpose of this study is to study the effects of abrasive tools on mild steel surface by using three parameters (depth of cut, table speed, and mode of dressing). This study was conducted by using surface grinding machine. Taguchi method was employed as an analysis tool for this study. Total series of experiments performed was 9 set for each grinding wheels (Silicon Carbide and Aluminium Oxide). Statistical software was used to predict the surface roughness. To validate the prediction result, experimental values compared. Result showed that lower depth of cut, lower table speed and lower mode of dressing produced better surface finish. For the abrasive tools used, the Aluminium Oxide wheel produced lower value of surface roughness compared with the Silicon Carbide wheel. The predicted result showed that depth of cut, table speed and dressing mode are significant parameter in influencing of surface roughness.